Training of prosocial skills to migrant groups through serious games - TOUNTOPOULOU, MARIA; Drosos, Nikos; Triantafillopoulou, Maria-Eirini; Vlachaki, Fotini; Daras, Petros; Vretos, Nicholas; Lelis, Athanasios (Advances in Social Sciences Research Journal, 2021)
Due to forced migration migrants, asylum seekers and refugees finding themselves in a new cultural environment and trying to build a new life, they need to feel affiliated, to achieve peer acceptance among natives and diverse migrant groups. Such affiliation needs can be achieved by tailored training interventions aiming to promote the development of prosocial skills of cultural diverse groups, as alternative actions to facilitate better migrants’/asylum seekers/refugees’ integration into the host society. The scope of this survey is to study the short-term effects of a social skills and prosocial behaviour training for adult migrants, refugees or asylum seekers. The method is based on the theory of prosociality and explores the effectiveness of a prosocial game in the development of prosocial skills, which are considered important for the social and emotional wellbeing and smoother integration of migrant groups in the new host community. A pre-test-post-test design was used, assigning 110 migrant participants to either an experimental or a control group and comparing them on their prosocial skills as evaluated through the NADINE questionnaire. Those who played the game significantly improved in their teamwork and interpersonal skills. Although further research should be made on the use of serious games in Social Emotional Learning (SEL) in migrant adults, this study adds to the research literature, supporting the potential of a game-based SEL intervention for effectively assisting migrant groups develop their prosocial skills and facilitating their better integration into the host society.